Embracing Collaboration through the Lens of Exceptional Needs Dance: A Mixed Methods Study. Issue 2 (2nd April 2020) - Suppo, Jennifer L.; Swank, TaMara
ABSTRACT: This article provides an overview of a proactive approach to collaboration for both dance and teacher education. Collaboration was examined through the lens of assisting children with disabilities to reach their maximum potential in the art of dance. The purpose of the research project was to examine pre-service teachers, in both dance and teachers' education, perceptions of working in collaboration with one another and with families of children with disabilities. The researchers also sought insight as to the information the pre-service teachers would learn regarding working with children with disabilities. University student perceptions were obtained through the use of a survey and weekly reflective journals. Additional feedback came in the form of the researchers' direct-observation notes and from parent feedback. The university students reported an overall positive learning experience. The researchers discussed what was learned through the experience, and they provided future implications.